KOMUNIKASI KEPALA MADRASAH DALAM MENINGKATKAN PRESTASI BELAJAR SISWA Studi Kasus di MTs Al-Ittihadiyah Medan - Abdul Mukmin (Universitas Islam Negeri Sumatera Utara Medan, 2017)
ABSTRACT The study aimed to find out how communication headmaster, the research was conducted in MTs Al- Ittihadiyah Medan. This study uses qualitative research. It is based on the consideration that this study reveals headmaster communication, qualitative research is a research procedure that produces descriptive data in the form of words written or spoken of people whose behavior can be understood. The subject of research directed to the search data from the headmaster, assistant headmaster, teachers and staff as well as parents of students in MTs Al- Ittihadiyah Medan. The data collection was obtained by observation, interview and documentation study.The findings of this study as follows: 1.Communication headmaster to the maid headmaster and the teachers who terjain well and conduct meetings with the regular program, communicate to improve achievement by way of enforcing discipline in a consistent, encourage subordinates to follow the scientific activities, educational seminars, workshops and attention to the activities eskskul outside school , advocated in following the race outside the school for the students' ability megukur communication means head headmaster proportional to student achievement seen from the graduation of students reached 100%. But not always visible kedisipilanan was carried out well, because the high looks for students coming late and still look less than the maximum in the learning process. 2. Communication headmaster with parents in improving presasi students, the communication is only a short stroll the category of less as expected because the communication that exists so far only once in three years with the agenda of a meeting with the new students, parents only coordinate and communicate to the homeroom teacher madrasah classes. But the category is less visible and intertwined in communication between the headmaster with parents. Keyword: communication, head master, learning achievement